Physical, Chemical, and Organoleptic Characteristics of Tempeh Cookies - Nurul Hidayah; Amelya Aprilliani Yolanda (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2025)
Cookies are widely consumed snack options made primarily from wheat flour. Alternative materials, such as tempeh flour, are needed to replace wheat flour in the production of cookies. Tempeh contains high levels of protein and crude fiber. This research aims to determine the effect of wheat flour and tempeh flour formulations on the physical, chemical, and organoleptic characteristics of cookies. This research employed a one-factor Completely Randomized Design (CRD), with variations in wheat flour and tempeh flour (F1, 100% wheat flour: 0% tempeh flour), (F2, 75%: 25%), (F3, 50%: 50%), and (F4, 25%: 75%). A total of 31 untrained panelists carried out organoleptic evaluations on the product. The analyzed physical and chemical properties include moisture content, ash, protein, fat, carbohydrates, crude fiber, and texture. Organoleptic tests include taste, color, aroma, hardness, crispness, aftertaste, and overall impression. Data analysis was performed using One-way ANOVA at a 5% significance level, followed by Duncan's post-hoc test. Results indicate that the different formulations of wheat flour and tempeh flour significantly affect the moisture content, fat, protein, carbohydrates, crude fiber, hardness, crispness, and organoleptic properties of cookies. The best cookie formulation was obtained at F4 (25% wheat flour: 75% tempeh flour), with the highest protein and crude fiber content of 16.10% and 12.36%, respectively. This finding had implications for reducing dependence on imported wheat flour and encouraged the diversification of local food products based on fermented soybeans with high protein and fiber content.